2016
DOI: 10.1186/s12931-016-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 expression in chronic obstructive pulmonary disease: relation to acute exacerbations and airway remodeling

Abstract: BackgroundRecent studies suggest that YKL-40, also called chitinase-3-like-1 protein, has been implicated in the pathogenesis of various inflammatory diseases. It is currently unknown, however, whether YKL-40 plays a role in acute exacerbations of chronic obstructive pulmonary disease (AECOPD) and airway remodeling.MethodsWe evaluated serum YKL-40 levels in patients with AECOPD (n = 37) and stable COPD (n = 44), as well as in controls (n = 47). The association between YKL-40 expression and airway remodeling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 42 publications
2
46
0
2
Order By: Relevance
“…27,61,62,94,95 It has been postulated that it could be related to higher macrophage and neutrophil CHIT1 and YKL-40 expression in COPD patients. 27,36,96 Recent studies showed that the release of CHIT1 is stimulated by interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), granulocyte-macrophage colony-stimulating factor (GM-CSF), lipopolysaccharide (LPS) as well as toll-like receptor (TLR) and nucleotidebinding oligomerization domain (NOD)-2 activation. [97][98][99] The exposure of alveolar macrophages from smokers with and without COPD to CHIT1 resulted in the production of IL-8, MMP-9 and MCP-1, cytokines said to be involved in tissue inflammation, alveolar destruction, and fibrosis.…”
Section: Chitinases and Clps In Patients With Copdmentioning
confidence: 99%
See 2 more Smart Citations
“…27,61,62,94,95 It has been postulated that it could be related to higher macrophage and neutrophil CHIT1 and YKL-40 expression in COPD patients. 27,36,96 Recent studies showed that the release of CHIT1 is stimulated by interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), granulocyte-macrophage colony-stimulating factor (GM-CSF), lipopolysaccharide (LPS) as well as toll-like receptor (TLR) and nucleotidebinding oligomerization domain (NOD)-2 activation. [97][98][99] The exposure of alveolar macrophages from smokers with and without COPD to CHIT1 resulted in the production of IL-8, MMP-9 and MCP-1, cytokines said to be involved in tissue inflammation, alveolar destruction, and fibrosis.…”
Section: Chitinases and Clps In Patients With Copdmentioning
confidence: 99%
“…Allergen and/or cigarette smoke (CS) exposure have been shown to trigger YKL-40 expression in several cell types (especially neutrophils, macrophages and epithelial cells). 69,92,93,95,96 The induction of YKL-40 expression and secretion may be mediated by various mediators, including interleukin (IL)-1,-13,-17A,-18 and TNFα. 65,69,95,[104][105][106] YKL-40 induces the production of proinflammatory and profibrotic mediators, ultimately resulting in tissue inflammation, alveolar destruction and remodeling.…”
Section: Chitinases and Clps In Patients With Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ugyanezt észlelték tüdőszövetben immunhisztokémiával történő kvantitatív mérés során. Eredményeik megerősítik, hogy az YKL40 protein fontos szerepet játszhat a COPD patogenezisében, a légúti gyulladásban és a remodellingben, így alkalmas COPD-biomarker lehet [20].…”
Section: A Copd Közelmúltban Felfedezett Fehérje Biomarkereiunclassified
“…Concluziile acestui studiu au fost: creşterea nivelului seric de YKL-40 al pacienţilor cu exacerbare acută a BPOC -s-a demonstat că nivelul seric al YKL-40 la pacienţii fumători cu BPOC a fost mai mare decât la fumătorii care nu aveau BPOC (12,30).…”
Section: Caracteristicile Chitinase-3-like Protein 1 (Chi3l1) -Ykl-40unclassified